Coronavirus and Value Pluralism: A Robust Ethical Perspective on a Pandemic - Haaz, Ignace (Journal of Dharma, 2020)
The fear of the largely unknown consequences of being exposed to coronavirus should have brought a more dynamic interplay of beliefs and opinions for those who in the footsteps of J.S. Mill believe that the limits of power, which can be legitimately exercised by society over the individual, is to prevent harm to others. It is surprising that not much debate or critical interaction has taken place on the choice of locking down most of the populace in 185 countries after the outbreak of COVID-19. The general lockdown, instead of testing and isolating the sick, can be seen as ‘a gross usurpation upon the liberty of private life.’ The axiological and ethical question confronting philosophers relates to the type and degree of authority needed during this period. As Mill claims, no general basic liberties can be respected overall without some previous and gradual evolution, that is, before other more specific liberties have met sustainable social practice. This essay reviews some of the problematic situations highlighting that no society is free or can achieve the objective of a fairly pluralistic set of values without a given social practice of these values, and shows how this logic of spreading of values unfolds in the context of the Coronavirus crisis.